2008
DOI: 10.1111/j.1399-6576.2008.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three doses of epidural fentanyl followed by bupivacaine and fentanyl for labor analgesia

Abstract: After a test dose of lidocaine-epinephrine, the three epidural fentanyl doses produced similar effective labor analgesia. However, epidural fentanyl 75 microg followed by epidural infusion of dilute bupivacaine and fentanyl produced longer duration of analgesia than fentanyl 50 microg followed by the same infusion, with no further prolongation when the dose of fentanyl was increased up to 100 microg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In another previous study, fentanyl 100 lg did not give any further advantage compared with fentanyl 75 lg in regard to duration of analgesia, suggesting that the duration of analgesia reaches a ceiling with a fentanyl dose of 75 lg. 21 In our results, fentanyl 100 lg was also not more advantageous than 75 lg from the aspect of extending duration of analgesia. However, our data are not sufficient to conclude which dose of fentanyl is ideal.…”
Section: Discussionmentioning
confidence: 74%
“…In another previous study, fentanyl 100 lg did not give any further advantage compared with fentanyl 75 lg in regard to duration of analgesia, suggesting that the duration of analgesia reaches a ceiling with a fentanyl dose of 75 lg. 21 In our results, fentanyl 100 lg was also not more advantageous than 75 lg from the aspect of extending duration of analgesia. However, our data are not sufficient to conclude which dose of fentanyl is ideal.…”
Section: Discussionmentioning
confidence: 74%
“…90,105 In a double-blind comparison of 50-, 75-or 100-lg loading doses of epidural fentanyl, followed by infusion of fentanyl plus bupivacaine, sadly only Apgar scores were recorded and did not differ between groups. 127 While epidural fentanyl may increase the number of episodes of maternal desaturation, such episodes have not been found to correlate with funic pH or NACS. 71 In a double-blind comparison of epidural bupivacaine infused alone or with fentanyl, the addition of moderate doses of fentanyl to epidural bupivacaine had a negligible effect on neonatal respiration.…”
Section: Variations In Neuraxial Drugsmentioning
confidence: 98%
“…Inability to walk may be related to the epidural drug concentration or dose, or the number of epidural doses over the course of labor 25 . Use of ultra‐light concentrations of bupivacaine 26,27 may have increased the ambulation rate among women in the toilet group. Previously, a study found that almost half the recruits could not bend the knee after 30 min of insertion of the epidural; however, voiding function was not reported 4 .…”
Section: Discussionmentioning
confidence: 99%